LAURA Completes the Osimertinib Treatment Jigsaw Puzzle of EGFR+ NSCLC from Stage IB to IV: Adjuvant Osimertinib Significantly Improves PFS and CNS Progression in Unresectable Stage III EGFR-Mutated NSCLC Compared to Placebo (LAURA, NCT03521154) - Luo FX; Arter Z; Ou SI; Nagasaka M (Lung Cancer: Targets and Therapy)
Faustine X Luo,1,2 Zhaohui Arter,1,2 Sai-Hong Ignatius Ou,1,2 Misako Nagasaka1– 3 1Chao Family Comprehensive Cancer Center, Orange, CA, 92868, USA; 2University of California Irvine School of Medicine, Orange, CA, 92868, USA; 3St. Marianna University School of Medicine, Kawasaki, JapanCorrespondence: Misako Nagasaka, University of California Irvine School of Medicine, 101 The City Drive South, Building 200, Room 410, ZOT 4061, Orange, CA, 92868, USA, Tel +1 714-456-5153, Fax +1 714-456-2242, Email nagasakm@hs.uci.eduAbstract: The current standard of care for unresectable stage III non-small cell lung cancer (NSCLC) involves a concurrent platinum-based doublet chemotherapy and chest radiotherapy, followed by consolidative therapy with durvalumab, an anti-programmed death ligand 1 (PD-L1) antibody, based on the PACIFIC trial (NCT02125461). However, the utility of durvalumab in EGFR-mutated lung cancer patients is questionable based on post-hoc analysis and multi-institutional retrospective analysis. Osimertinib is a third-generation EGFR-tyrosine kinase inhibitor (TKI) with proven clinical efficacy in NSCLC. Given that durvalumab showed no benefit in unresectable Stage III EGFR-mutated NSCLC, it is exciting that most recently, the LAURA trial has demonstrated promising outcomes with adjuvant osimertinib in unresectable, stage III EGFR-mutated NSCLC after definitive chemoradiotherapy with significant improvement in PFS compared to placebo. Furthermore, the LAURA trial demonstrates that osimertinib has a protective effect against distant metastases and CNS progression in this patient population. Here, we explore the results of the LAURA trial and how it transforms the standard-of-care treatment for patients with unresectable, stage III EGFR-mutated NSCLC moving forward.Keywords: stage III, chemoradiation, consolidation therapy, epidermal growth factor receptor, tyrosine kinase inhibitor